Two new species of Cilliba von Heyden from Poland, with discussion of the Cilliba cassidea (Hermann) species complex (Acari: Mesostigmata: Uropodina: Cillibidae) - Błoszyk, Jerzy; Stachowiak, Marcin; Halliday, Bruce (Zootaxa, 2006)
Two new species of mites are described from Europe on the basis of all developmental stages: Cilliba cassideasimilis sp. nov. and C. rafalskii sp. nov. (Acari: Uropodina: Cillibidae). Both of these species have been misidentified in the past as the closely related species C. cassidea, but these three species can be distinguished using morphological characters. Data on their geographical distribution and some remarks about ecology of both species are presented and discussed. New records of mites of the genus Cilliba are given.